KONFLIK BATIN TOKOH UTANA PADA NOVEL LELAKI HARIMAU KARYA EKA KURNIAWAN: PENDEKATAN PSIKOLOGI SASTRA - Putri Bekti Noviyanti; Rusdian Noor Dermawan (CARAKA, 2018)
This study aims to find out: 1) the plot in the Lelaki Harimau novel by Eka Kurniawan; 2) characters and characterizations in the Lelaki Harimau novel by Eka Kurniawan; 3) the setting or setting in the Lelaki Harimau novel by Eka Kurniawan; 4) inner conflict in the Lelaki Harimau novel by Eka Kurniawan; 5) causes of inner conflict in the Lelaki Harimau novel by Eka Kurniawan. This type of research is qualitative research. The research data is in the form of a unit of events in the form of sentences and paragraphs contained in the Lelaki Harimau novel. The research data source is Lelaki Harimau novel by Eka Kurniawan. The instrument of this research is that the researchers themselves are equipped with a set of theories. The research data collection technique is carried out by reading the entire contents of the novel, observing, and recording the data obtained. The research data analysis technique was carried out with qualitative descriptive techniques. The results of this study: 1) The flow in the novel Lelaki Harimau by Eka Kurniawan is a mixed plot; 2) Figure and character, the main character in the novel Lelaki Harimau by Eka Kurniawan is Margio with an honest, trustworthy, innocent and caring character; 3) The location in the Lelaki Harimau novel is 131, Surau, Warung Agung Sofyan, Rumah Anwar Sadat, Hutan, Rumah Margio, 4) The form of the main character's inner conflict in Lelaki Harimau Novel by Eka Kurniawan is due to the main character being born and raised in the environment families who are very deficient do not make the main character feel happy; 5) Factors that cause the inner conflict of the main character in Novel Lelaki Harimau by Eka Kurniawan, internal factors and external factors.